2003
DOI: 10.1096/fj.03-0096fje
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain expression in renal afferent and efferent arterioles: relationship to contractile kinetics and function

Abstract: The physiological role of smooth muscle myosin heavy chain (MHC) isoform diversity is poorly understood. The expression of MHC-B, which contains an insert at the ATP binding pocket, has been linked to enhanced contractile kinetics. We recently reported that the renal afferent arteriole exhibits an unusually rapid myogenic response and that its kinetic features allow this vessel to modulate tone in response to alterations in systolic blood pressure. In the present study, we examined MHC expression patterns in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 33 publications
5
37
2
Order By: Relevance
“…The DVR in the innermost 50% of the rat and kangaroo rat inner medulla also express little or no UT-B (15,49). However, functional studies in rats have shown that vasa recta from the deep papilla exhibit substantial urea Smooth muscle myosin heavy chain protein is expressed in renal arterioles (26,44), and its expression along the upper inner medullary DVR in the human kidney suggests that segments in the upper zone of the inner medulla have contraction and relaxation properties, as has been shown for DVR of the inner stripe of the outer medulla (32). The contractile properties of segments at deeper levels of the inner medulla, where smooth muscle myosin heavy chain protein expression is distributed more sparsely or is absent altogether, likely are different.…”
Section: Discussionmentioning
confidence: 99%
“…The DVR in the innermost 50% of the rat and kangaroo rat inner medulla also express little or no UT-B (15,49). However, functional studies in rats have shown that vasa recta from the deep papilla exhibit substantial urea Smooth muscle myosin heavy chain protein is expressed in renal arterioles (26,44), and its expression along the upper inner medullary DVR in the human kidney suggests that segments in the upper zone of the inner medulla have contraction and relaxation properties, as has been shown for DVR of the inner stripe of the outer medulla (32). The contractile properties of segments at deeper levels of the inner medulla, where smooth muscle myosin heavy chain protein expression is distributed more sparsely or is absent altogether, likely are different.…”
Section: Discussionmentioning
confidence: 99%
“…Although degradation of the cardiac jelly by hyaluronidase allows looping to continue in the rat and chick models (Baldwin and Solursh, 1989;Linask et al, 2003b), this enzyme exposure would be expected to break down proteoglycans, but would not be expected to degrade integrin-glycoprotein interactions within the myocardial basal lamina that becomes closely apposed to the endocardium in these experimentally treated embryos. The association of NMHC-II proteins with mechanotransduction is seen in other systems, as for example, in relation to cilia in the inner ear for transmission of sound waves and in relation to afferent and efferent arterioles in the kidney in detection of blood flow pressure (Shiraishi et al, 2003;Marigo et al, 2004). Recently, with regard to mesenchymal stem cells the nonmuscle myosins are shown to .5 hearts of Nodal ϩ/ϩ and Nodal ⌬600/⌬600 embryos.…”
Section: Nonmuscle Myosin II Proteins and Heart Loopingmentioning
confidence: 99%
“…The myocytes of the preglomerular afferent arteriole and postglomerular efferent arteriole differ remarkably in Ca 2ϩ entry mechanisms, myosin expression, and the mechanisms modulating vascular reactivity. [1][2][3][4][5][6] Further regional heterogeneity has been noted for ion channel expression in the juxtamedullary versus cortical efferent arterioles 7 and in the activating mechanisms of the contractile pericytes of the descending vasa recta. 8 For example, angiotensin II (AngII) responses of the afferent arteriole and descending vasa recta involve membrane depolarization and voltage-gated Ca 2ϩ entry and are attenuated by L-type Ca 2ϩ channel antagonists.…”
mentioning
confidence: 99%